ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEREKONOMIAN DAN INVESTASI DI SUMATERA BARAT - Eriawati, Yossi; Amar, Syamsul; Idris, Idris (Jurnal Kajian Ekonomi, 2015)
This article focused on analyze (1) Effect of the Economic, net ekspor, consumtion,   infrastructure economi and invetment in West Sumatera. (2) The influence of investment, inflation, interest rate, and infrastructure economic in West Sumatera. Data used time series of 1983 - 2012. This article use analyzer model equation of simultaneous with method of  Least Squared (LS). The result of research concludes that (1) the net ekspor have a significant and positive impact on the economic, consumtion have significant and positive impact on the economic, infrastructure econimic  significantly and positive on the economic, and investment is significant and positive on the economic in West Sumatera. (2) The interest rates is not significant and negative on the investment, inflation is not significant and negative on the investment, and infrastrukture economic a significant and positive on the investment in West Sumatera. Keywords :economic, investment, net ekspor, consumtion, inflation, interest rates, and economic infrastructure